ENVIRONMENTAL CONDITIONS AND THE BACTERIAL COMMUNITY IN CORAL MUCUS AT COAST OF CAT BA AND LONG CHAU ISLAND, VIETNAM - Thu, Pham The; Ngai, Nguyen Dang; Ha, Bui Thi Viet (Vietnam Journal of Marine Science and Technology, 2014)
Coral reef ecosystems have been strongly reduced, in which disease is one of the causes affecting coral reefs in worldwide. The cause determination of coral disease still faces many difficulties. Understanding the causes and pathogenic mechanisms, including micro-organisms is very important. Determining the influence of environmental conditions on the change of coral-bacterial community characteristics is one of the steps to find out the conditions of coral disease outbreak. Therefore, mucus from 12 coral species in two areas with a big different of chemical and physical environmental conditions (Long Chau and Cat Ba) was studied. Molecular methods such as SYBR Gold staining, flow-cytometry, Biolog Ecoplate and denaturing gel electrophoresis were used. The study results showed that the characteristics of bacterial communities (cell density, morphology group rate, heterotrophic bacteria and Vibrio) in coral mucus between Cat Ba and Long Chau Island were not significantly different, but their functional activities (respiration, absorption of organic matter) were potential affected by environmental conditions. Environmental conditions in coast of Cat Ba and Long Chau Island in this study were not indicated the difference in bacterial pathogenicity for coral. This result is the initial scientific basis for the establishment of further research being more effective, more authentic and more concise to assess bacterial pathogenicity for coral at areas with different environmental conditions.